The response of exospheric neutral hydrogen to weak geomagnetic disturbances between June 12 and 29, 2008 - Zoennchen, Jochen H.; Cucho-Padin, Gonzalo (Frontiers in Astronomy and Space Sciences, 2025)
Stereoscopic remote sensing observations of terrestrial far ultraviolet (Lyman-α at 121.6 nm) emissions at solar minimum have been used to retrieve the time-dependent response of the exospheric 3-D neutral hydrogen (H) density at radial distances of 3–6 Earth radii (Re) to weak geomagnetic disturbances. This study includes continuous observations from the Lyman-α detectors (LADs) onboard NASA’s Two-Wide angle Imaging Neutral-atom Spectrometers (TWINS) 1 and 2 satellites between June 12 and 29, 2008, which covers two minor geomagnetic storms (June 15 and 25). For both storms, we derived the 3-D H-density distributions from prior and during-storm data with 12 h time intervals. The inversion is based on our new H-density EXPGRID model and incorporates the effects of Lyman-α absorption within the exosphere and Lyman-α re-emission from Earth’s albedo. We found that the H-density distributions at 3–6 Re are highly variable. They are correlated and vary in phase with exobase temperatures (from Naval Research Laboratory mass spectrometer and incoherent scatter (NRLMSIS)) during the geomagnetic events. Furthermore, the time dependency and amplitude of the H-density enhancement and the kp index were found to be similar. Because the kp index is assumed to be correlated with the varying size of the plasmasphere, this finding supports theories of physical interaction between the neutral exosphere and the plasmasphere. The disturbances with a significant effect on the neutral H atoms are initiated by a prior increase of the solar wind flow pressure and exobase temperatures (in particular, over the poles). Our time-dependent 3-D results indicate that the H-atom enhancement is not uniformly distributed over the shells. Instead, we found asymmetries (i.e., dawn/dusk near the ecliptic) and temporal evolving zones of regionally strong enhanced H densities. Among the first affected regions after onset are the vicinities of the geotail (at lower distances) and the North Pole (at upper distances). A ∼40% exobase temperature increase (NRLMSIS) at the South Pole on June 15 correlates with a strong H-atom enhancement in the southern hemisphere later this day. Finally, both storms show, at the upper distance, a remarkably delayed enhancement (peak values as late as ∼2 days after onset) of the H atoms density near the sub-solar point (dayside “nose” region).